High yield embryology / Ronald W. Dudek - Dudek, Ronald W.
Prefertilization events -- Week 1 (days 1-7) -- Week 2 (days 8-14) -- Embryonic period (weeks 3-8) -- Placenta, amniotic fluid, and umbilical cord -- Cardiovascular system -- Digestive system -- Urinary system -- Female reproductive system -- Male reproductive system -- Respiratory system -- Head and neck -- Nervous system -- Ear -- Eye -- Body cavities -- Pregnancy -- Teratology.